2012
DOI: 10.4209/aaqr.2011.12.0240
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Micro Environment in the Han Yang Mausoleum Museum

Abstract: As a first underground museum in the world, whole sealed glass system is adopted in the Han Yang Mausoleum Museum to protect relics from the destruction by microbe and pollution in the atmosphere and to provide visitors a wonderful environment for enjoying the fantastic artwork closely from different angles. This study shows that, this method cannot completely stop relics from the destruction. The main reason is that, in the museum, the microbe growth and pollution spread are fairly significant to affect the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A number of studies have indicated that indoor air pollutants with chemical (Lu et al, 2006;Chen et al, 2009) and biological (Ortiz et al, 2009;Wan et al, 2011;Napoli et al, 2012) natures pose potential hazards to patients, medical staffs, and visitors in hospitals. Sophisticated simulations through computational fluid dynamics for indoor air contamination and control design have also been developed (Panagopoulos et al, 2011;Cao et al, 2012). In particular, Ping-Yun Huang and Zhi-Yuan Shi made equal contribution to the study.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that indoor air pollutants with chemical (Lu et al, 2006;Chen et al, 2009) and biological (Ortiz et al, 2009;Wan et al, 2011;Napoli et al, 2012) natures pose potential hazards to patients, medical staffs, and visitors in hospitals. Sophisticated simulations through computational fluid dynamics for indoor air contamination and control design have also been developed (Panagopoulos et al, 2011;Cao et al, 2012). In particular, Ping-Yun Huang and Zhi-Yuan Shi made equal contribution to the study.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of a design of ventilation around a church organ shows a similar decay of velocity, from 3 m/s at the input to a few centimetres per second in the spaces between the organ pipes [27]. This is a common feature of air motion indoors: after leaving the ventilation output, the air velocity decays by at least one order of magnitude, sometimes two, in a few meters, as seen in many of the reviewed articles [33,62,63].…”
Section: Sources Of Low Velocity Flowsmentioning
confidence: 79%
“…Even in the underground exhibition hall of Hanyangling Museum, China, opened in 2006, where physical divisions exist between visitor passages and the exhibition hall and many other technical measures have been utilized for the preservation of relics, the relics are still not preserved as well as expected. Slight surface cracking and weathering have been found on the pottery figurines, and air pollutants such as SO 2 and NO x have been found on the relics' side of the enclosed hall [8][9][10]. An investigation organized by China's State Administration of Cultural Heritage X. Luo et al / Journal of Cultural Heritage xxx (2015) xxx-xxx reveals that there are more than 3000 museums in China, among which approximately 51% of the collections are suffering deterioration or even ruin due to improper preservation environments [11,12].…”
Section: Introductionmentioning
confidence: 99%